Towards Sustainable Development: A Study of Cross-Regional Collaborative Carbon Emission Reduction in China - Xiumei Sun; Haotian Zhang; Xueyang Wang; Zhongkui Qiao; Jinsong Li (Sustainability, 2022)
Exploring a scientific and reasonable cross-regional carbon emission reduction path in China is essential to achieving sustainable development and the carbon neutrality target. This study constructs a simulation model of China’s cross-regional carbon emission reduction (CER) system and adopts a multi-agent approach to simulate cross-regional CER scenarios to predict the pathway. The conclusions are as follows: (1) under the national unified CER policy scenarios, carbon emissions are on a continuous growth trend with fast economic growth not matching emission reduction efforts in Scenario I. Scenario II has a lower economic scale, and carbon emissions peak in 2029. Scenario III has smooth economy and reaches the carbon emission peak in 2026. The economy of Scenario IV grows fast, carbon emissions grow slowly, and the peak does not appear in 2030. (2) In three scenarios with provinces as the main agent for CER, if provinces sacrifice the economy to strengthen CER, the peak of carbon emissions will appear in 2020. While the economy of non-synergistic and synergistic CER scenarios in each province is growing steadily, the peak in two modes is reached in 2026 and 2032. The peak is reached four years earlier in 2026 in the synergistic model and 2032 in the non-synergistic model, and the economic growth of some energy-intensive provinces slows down. (3) The synergistic low-carbon model is best for balancing economic development and carbon emission control. Policy recommendations are presented based on the above findings for China’s CER and sustainable development.